DESAIN PEMBELAJARAN BILANGAN BERPANGKAT BERBANTUAN PERMAINAN MATCHING-OPERATION UNTUK MEMFASILITASI RETENSI DAN MINAT BELAJAR PESERTA DIDIK - Lilis, Lilis Patimah; Muslim, Farhan Maulana (Universitas Islam Nusantara, 2024)
This study aims to develop a learning design for rank numbers with the help of Matching-Operation game to facilitate students' retention and interest in learning. This research uses Design Research method with ADDIE design. The results showed that the learning design of power numbers with the help of the Matching-Operation game was included in the very valid category. Retention and interest in learning of students fall into the high and very high categories after carrying out the learning process using the Matching-Operation game. Based on these results, it can be concluded that the learning design of power numbers with the help of the Matching-Operation game can facilitate students' retention and interest in learning.